ANALYSIS OF SCIENTIFIC PRODUCTION IN STREET SPORTS WITH ACROBATIC COMPONENTS - Yeray Rodriguez-Redondo; Angel Denche-Zamorano; Maria Mendoza-Muñoz; Adsuar Jose C.; Kiko Leon (University of Ljubljana Press (Založba Univerze v Ljubljani), 2024)
In recent years, the number of practitioners of disciplines such as parkour, break dance or calisthenics (freestyle or street workout) has increased. These disciplines share common characteristics, such as an unregulated street origin and a focus on acrobatics. This study aimed to analyze the state of scientific publications related to these acrobatic street sports. A bibliometric analysis was conducted, applying traditional bibliometric laws to scientific documentation found in journals indexed in WoS and Scopus. Data processing and visualization were performed using Bibliometrix and Excel. A total of 199 articles published between 1984 and 2024 were identified, indicating exponential growth. Among these, 139 papers were related to parkour, 48 to breakdance, and 12 to street workout. A review of 158 journals revealed that they contained related publications, although their distribution did not conform to Bradford's model, showig only two areas. Among 417 authors identified, 22 were deemed prolific and 12 prominent. France emerged as the most prolific country, followed by the USA. The 553 author keywords were categorized into three groups, each associated with one of the sports. The 26 most cited papers were selected as relevant, demonstrating a correlation between the increase in publications and the popularization of these sports, largely due to television exposure. The "International Journal of Sport Policy and Politics" emerged as the most prolific journal. The most relevant authors identified in each sport were Signey Grosprêtre (parkour); Max Daniel Kauther and Christian Wedemeyer (breakdance); and Javier Sanchez-Martinez (street workout).